2001
DOI: 10.1506/cpku-r1dw-vw7m-u158
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Affect on Managers' Capital‐Budgeting Decisions*

Abstract: In this paper, we propose that affective reactions are integral to accounting decision contexts like capital budgeting, and that researchers must jointly consider affect and cognition to better understand accounting decision makers' behavior. We argue that interpersonal relationships are characteristic of many capital‐budgeting contexts, and that these relationships can lead to emotional affective reactions. For example, reactions such as frustration and anger may result if a manager is treated unfairly by ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 28 publications
1
79
0
2
Order By: Relevance
“…As discussed previously, Fisher et al (2000Fisher et al ( , 2002a found that fairness issues caused negotiators to make concessions, even when it was not in their best interests, and that perceptions of procedural fairness affected budgetary performance. Kida et al (2001) and Moreno et al (2002) found that perceptions of unfair treatment affected managers' capital investment decisions, and Williamson (2008) found that employees who perceived their environment to be fair contributed more to firm value. Cohen et al (2007) found that employees were less likely to invest opportunistically when they perceived the action to be unfair, even when they had both the opportunity and incentive to do so.…”
Section: S -Management Accountingmentioning
confidence: 99%
“…As discussed previously, Fisher et al (2000Fisher et al ( , 2002a found that fairness issues caused negotiators to make concessions, even when it was not in their best interests, and that perceptions of procedural fairness affected budgetary performance. Kida et al (2001) and Moreno et al (2002) found that perceptions of unfair treatment affected managers' capital investment decisions, and Williamson (2008) found that employees who perceived their environment to be fair contributed more to firm value. Cohen et al (2007) found that employees were less likely to invest opportunistically when they perceived the action to be unfair, even when they had both the opportunity and incentive to do so.…”
Section: S -Management Accountingmentioning
confidence: 99%
“…For example, Kida et al (2001) find that affective reactions cause managers to select capital investment options that have lower net present values than other investment options under consideration. Moreno et al (2002) find that the effect of gain/loss domains on managers' capital investment decisions is overwhelmed by managers' affective reactions.…”
Section: Capital Investment Decisionsmentioning
confidence: 99%
“…A number of experimental studies document that managers' capital investment decisions are influenced by factors of a non-economic nature (Kida et al, 2001;Moreno et al, 2002;Sawers, 2005;Staw, 1976), but it is not clear whether the results of those studies persist in real-world settings that involve actual economic consequences to both managers and their firms. This study identifies an additional determinant of managers' capital investment decisions (i.e., firms' depreciation method choice) that is of non-economic nature and provides archival evidence that this determinant influences managers' capital investment decisions.…”
mentioning
confidence: 99%
“…For example, when applying a balanced scorecard (BSC) approach to the capital budgeting decision, a balance scorecard strategy mandates decision disaggregation into independent elements, assessment of each disaggregated element and then reaggregation of element assessments to yield a final decision. Thus, the decision-maker must evaluate each investment option on multiple criteria and then apply importance weights to each criterion (Anderson, 2003;Kida, Moreno, & Smith, 2001). Having to choose between alternatives with different features requires value trade-offs and is a definition of a difficult decision task (Beattie & Barlas, 2001;Kaplan, Petersen, & Samuels, 2007;Lazarus, 1991;Luce, 1998;Sawers, 2005).…”
Section: Introductionmentioning
confidence: 99%